Functional and radiological results of percutaneous K-wire aided Métaizeau technique in the treatment of displaced radial neck fractures in children - Çevik, Nazan (Acta Orthop Traumatol Turc, 2018)
OBJECTIVES: The aim of the present study was to determine the radiological and functional results and the efficiency of paediatric radial neck fracture fixation following reduction with the Métaizeau technique together with percutaneous K-wire applied under fluoroscopy to ensure minimum soft tissue damage. METHODS: The study included 20 patients with Judet Type 3, Type 4a and Type 4b fractures operated on with the Métaizeau technique aided by percutaneous K-wire between 2007 and 2014. The mean age of the patients was 9.75 years (range, 4–13 years). Mean preoperative angulation was measured as 52.4° (range, 35°–85°). The average postoperative follow-up time was 34.65 months (range, 13–84) months. Postoperative radiological evaluations were made according to the Ursei classification and functional assessment with the Tibone – Stoltz classification system. RESULTS: Radiologically, the difference between preoperative and postoperative radius head angulation was found statistically significant (p0.001). In the clinical assessment of injured and uninjured arms, there was no statistically significant difference between flexion-extension (p = 0.330) and supination-pronation range of motion (p = 0.330) and carrying angles (p = 0.094). According to the radiological Ursei evaluation, 17 (85%) patients were in perfect condition and 3 (15%) were good. In the classification of Tibone – Stoltz, 16 (80%) patients were evaluated as perfect, 3 (15%) as good and 1 (5%) as fair. CONCLUSION: From the results of this study and related literature, the use of the Métaizeau technique in displaced radial neck fractures requiring surgical treatment in children can be recommended since it creates minimum damage to the soft tissue, is easy to apply and the results are satisfactory. LEVEL OF EVIDENCE: Level IV, therapeutic study.